KARAKTERISTIK DODOL UBI JALAR UNGU (Ipomoea batatas blackie) DENGAN VARIASI PENAMBAHAN TEPUNG RUMPUT LAUT - Erilia Vitriasari; Agus Suyanto (Jurnal Pangan dan Gizi, 2012)
Dodol is a processed food made of a mixture of glutinous rice flour, palm sugar, and coconut milk which is boiled until be condensed so it can be sliced. Sweet potatoes contain anthocyanins ranging from 519 mg/100 g fresh weight. Seaweed contains carrageenan. It has a chewy texture, therefore it is very precise in the manufacture of Dodol. The purpose of this study is to determine of physical characteristics (yield, color stability, and resilience), chemicals (levels of carbohydrates, fiber, and calcium), and organoleptics (texture, flavor, color, and taste). The variations of seaweed flour is 0%, 10%, 20%, 30%, and 40%. The research design of this study is using a completely randomized design. Physical and chemical characteristics using Anova statistical were analyzed and further tested with LSD while organoleptic using Friedman and Wilcoxon further examined. The results showed that yield is 109.14%. Decreased color stability is 70.29 L. Increased elasticity is 1828.96 N / mm. Contests of carbohydrates, fiber and calsium 10.01 g/100, g/100 6.09 and 10.40 mg/100. Dodol purple sweet potato flavor down except textures. Thus, the results can be concluded that the addition of seaweed flour will significantly on physical characteristics, chemical, and organoleptic. Keywords : dodol, purple sweet potatoes, seaweed flour, physical, chemical and organoleptic.